Effects of Ho: YAG Laser (2100nm) in Prostate Tissue: An in vitro Study - Mahmood, Ali S.; Khattab, Omar S.; Tanno, Saba Y. (Iraqi Journal of Laser, 2019)
Benign prostate hyperplasia (BPH), non-cancerous enlargement of prostate, is the most prevalent disease entity in elderly men. BPH affects 40% of men after the age of 60year worldwide. BPH causes problems for patients with significant lower urinary tract obstructive symptoms, if not responding to medical therapy, surgical intervention is instituted. One method of the treatment of symptomatic BPH is laser prostatectomy. The understanding of tissue effects by laser radiation is very important for the safe clinical application of laser. Objective: study the 2100 nm Ho: YAG laser gross tissue effects in the prostate at different laser dose settings in an vitro model prostate tissue samples harvested from same specimen of open surgery prostatectomy. Materials and methods: Specimen of same open surgery prostatectomy was sectioned into six samples preserved in 4% formalin solution. Laser irradiations were performed in ambient air at room temperature. Samples exposed to varying laser dose parameters using pulsed Ho: YAG laser. The laser settings consisted of energy per pulse (0.3, 0.5 and 1 J), and pulse repetition rate (10 and 25 Hz) in single or double pulse mode. Pulse duration was 350 μs. Laser radiation was delivered using laser fibers with an optical core diameter of 550 μm. Main evaluation criteria of the Ho::YAG laser performance in prostate tissue was made by visual gross appearance of the effects of incision, cutting, vaporization, ablation and coagulation properties. Results: high laser dose setting revealed ablation, vaporization, incision, and cutting performance. Also there was clear evidence of coagulation zone. There was no clear appearance of carbonization. Sometimes minimum carbonization effect noticed. Ablation of prostate tissue was achieved by low dose setting. High and Low settings were responsible for coagulation effect. Conclusion: different dose parameters including energy per pulse, pulse repetition rate and in single or double pulse mode provide an effective way for ablation, vaporization, incision, cutting and coagulation effects in the prostate tissue.